Loss and Trauma in Shaping Sarat's Character in El Akkad's American War - Pratama, Bayu Putra; Ikrima Sa'adah, Sufi (Universitas PGRI Madiun, 2025)
This research aims to analyse how trauma shapes Sarats character in the novel American War by Omar El Akkad. The researcher used a descriptive qualitative method to analyse the data. The data were collected by focusing on the narrative text in the novel that depicted the traumatic events and the radicalism acts by Sarat. The researcher analysed the data by providing the descriptive context of the data. In the novel, the researcher describes several accidents, such as Sarats parents death, losing her home, the massacre in Camp Patience, and the persecution she received in prison, that caused Sarats trauma. This trauma somehow led to Sarats radical acts and attitude change. There are at least 3 radical acts done by Sarat that were mentioned in this research. It is the killing of a North General Soldier, the killing of the Sugarloaf Detention Centres guard, and the homicide of Sarat to spread the dangerous virus. By analysing and connecting the dots between the trauma and future radical acts, the researcher found that Sarats trauma and losses she got in her early life indeed had triggered her radicalism acts.